Prevalence of pre-hypertension and its relationship with body mass index among the medical students of Agartala government medical college - Debbarma, Aghore; Bhattacharjya, Himadri; Mohanty, Arpita; Mog, Chanda (International Journal of Research in Medical Sciences, 2017)
Background: Body Mass Index (BMI) is found to be positively co-related with the increased prevalence of elevated blood pressure among younger individuals. The present study was designed to find out the prevalence of pre-hypertension and its relationship with BMI among the medical students. Methods: A cross-sectional study was conducted during June - July 2013 among 306 medical students of Agartala government medical college, chosen by stratified random sampling. Results: Prevalence of pre-hypertension, hypertension and optimum BP were found to be 45%, 4% and 51% respectively. Mean BMI was found to be 21.68 ± 3.55, 80% of the students had ideal waist hip ratio, 19% were underweight, 61 % had normal weight, 18 % were overweight, and 2% were found to be obese. Pre-hypertension was significantly more prevalent among the senior medical students (χ2 = 4.933, P = 0.026), males (χ2 = 10.826, P = 0.001) and those who had family history of hypertension (χ2 = 4.228, P= 0.039). Pre-hypertension was significantly higher among the obese medical students (χ2 = 6.941, P = 0.008). Logistic regression analysis revealed that medical students had 12.8% more chance of having pre-hypertension with one unit increase in their BMI. Conclusion: Prevalence of pre-hypertension among medical students is high and BMI is found to be significantly associated with pre-hypertension. Hence it can be used as an effective tool for predicting pre-hypertension and development of hypertension among medicos later on.